Continuing processes of uneven development in post-apartheid South Africa. Issue 2 (3rd April 2022) - Smith, Jennifer L.
ABSTRACT: Despite the multitude of political and economic changes in post-apartheid South Africa, poverty is being relocated from former Bantustans and townships to peri-urban areas. Examining historical economic and planning policies, and changing social relations near Polokwane, South Africa, this research provides an uneven development analysis of South Africa's post-apartheid urban landscape. A mixed methods approach is applied to demonstrate new spatial configurations of inequality within and between peri-urban areas. The research concludes that neo-liberal urbanisms, local labor relations and local planning policies combined with the coproduction of peri-urban landscapes, shape new patterns of uneven development in post-apartheid South Africa.